Contributions of the institutions for the nursing professionalization: integrative review (2010-2020) in the light of freidsonian conceptions - Natália Maria Freitas e Silva Maia; Francisca Aline Amaral da Silva; Agostinho Antônio Cruz Araújo; Ana Maria Ribeiro dos Santos; Fernanda Batista Oliveira Santos; Pacita Geovana Gama de Sousa Aperibense (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To analyze the contributions of the Brazilian Nursing Association and the Federal and Regional Nursing Councils in the literature for the professionalization of nursing in the light of Eliot Freidson’s theoretical conceptions. Methods: Integrative review of the literature, of socio-professional historical interest, carried out from June to November 2021, through the question: How did professional associations contribute to the professionalization of Brazilian nursing according to the literature from 2010 to 2020? The evidence were organized in a synoptic table, which allowed the construction of a conceptual map. Results: In the 23 selected studies, the professional associations presented scientific, social and political contributions, which shape the professional field of nursing, enabling knowledge/expertise, autonomy and self-regulation. Final considerations: The efforts of these institutions reaffirm nursing as an academic and consulting profession, capable of exerting control over the essence of nursing work. They strive to consolidate nursing as a legitimate professional field of health in Brazil.